Examining 50 Years of Research on Administration in the Canadian Journal of Higher Education - Lavigne, Eric (Canadian Journal of Higher Education / Revue canadienne d'enseignement supérieur)

(untitled) (Canadian Society for the Study of Higher Education, 2021)
As the Canadian Journal of Higher Education celebrates its fiftieth anniversary, this article takes the measure of the researchpublished so far on higher education administration and reflects on future work. The study examined the 38 articles on highereducation administration published by the Journal between 1971 and 2020 to characterize how administration has been investigated and theorized since the Journal’s inception. The article discusses the topics that have captured the attention of scholars and the frameworks and methods they selected for their investigations. Overall, the body of work published by the Journal in its first 50 years of existence paints a nuanced portrait of higher education administration where administrators appear simultaneously powerless and powerful. The article suggests promising areas of inquiry based on its findings and discusses implications for editors, reviewers, and authors.